USAGE OF 4TH GENERATION POLYCOMPONENT PROBIOTIC IN ORDER TO PREVENT AND TREAT DISBIOTIC DISORDERS OF GASTRO-INTESTINAL TRACT - E. V. Komarova (Вопросы современной педиатрии)
The article covers the role of intestinal microflora in maintenance and regulation of all the vital body functions. The causes of intestinal microbiocoenosis and possibilities of probiotic usage in order to correct revealed disturbances are discussed in this article.